Improved germination of soybean seed treated with thiamethoxam under drought conditions - Cataneo, A. C. [UNESP]; Ferreira, L. C. [UNESP]; Carvalho, J. C.; Andreo-Souza, Y. [UNESP]; Corniani, N. [UNESP]; Mischan, M. M. [UNESP]; Nunes, J. C. (Ista-int Seed Testing Assoc, 2010)
The effect of thiamethoxam on germination of soybean (Glycine max L.) seeds cv. Pintado under water deficit was studied. When used as insecticide at the recommended level (100/100 kg seeds) in the treatment of soybean seeds. thiamethoxam accelerated germination. Soybean germination was delayed under lower water availability: however pretreatment of seeds with thiamethoxam reduced the negative effects of water deficit on such process.